Prenatal Attachment pada Kehamilan Remaja dengan Gangguan Penyesuaian dan Retardasi Mental Berat - Putri, Frilya Rachma; Rahmadianti, Mayniar Ayu (-)
Prenatal attachment is an abstract and unidirectional bond between parents and the fetus that develops during pregnancy. It is closely associated with how the mother utilizes her abilities and knowledge to organize and perform the duties related to her maternal role attainment. We report a case of 15 years old girl admitted to the emergency room with an official request of visum et repertum in January 2018 due to becoming suspected sexual violence victim. The history of present illness revealed a 15 y.o. girl G1P0A0, singleton, at 34-36W Estimated Gestational Age with condyloma acuminata. During her pregnancy, she described relatively negative feelings about her pregnancy including shame, anxiety, and anger. She felt lack of energy and motivation since she became aware of her pregnancy, therefore spent her most of her time on the bed. Her IQ-test showed a profound intelligence rate followed by a total score of Strength and Difficulty Questionnaire (SDQ) 16, and scored low in Prenatal Attachment Inventory (PAI) at 31. We concluded that PA scoring can be utilized as a predictor of mother-infant bonding quality after birth, thus the instrument will be beneficial as initial screening before choosing appropriate management for vulnerable population mother.